Pengaruh Konsentrasi Padatan Terhadap Kerugian Tekanan Aliran Lumpur - Ridwan, Ridwan (Universitas Gunadarma, 2014)
Mud is basically a mixture of solid particles and water forming a suspension. At the time of the mud is flowing through pipes, if the pressure of the flow is not high enough to overcome the drag/friction between particles and against the walls of the channels, then the system will not work properly and optimally. The pressure loss in each fluid flows needs to be recognized and calculated because it will affect the whole system performance. The purpose of the study is to observe the influence of concentration weight (Cw) to the pressure loss on the system. The test fluid is mud with two variations of Cw namely Cw 25% and Cw 50%, as well as, standard hydraulic fluid (Cw 0%). The test pipe used is acrylic pipe with inner diameter of 1” (25,4 mm) and length of 200 mm. The equipment composition is designed and manufactured, as well as equipped by measuring tools such as pumps (piston type), manometer, beaker glass, digital scales, tank shelters, stopwatch, data processing computer, etc. The result of analysis indicates that the higher concentration weight of mud, the bigger friction and pressure loss occuring in the same Reynolds number/speed comparisons. The pressure loss of mud flow with the speed of 0,5 m/sec to 0,65 m/sec contributes the lowest pressure loss.Keywords: Concentration weight, pressure, mud, manometer